2001
DOI: 10.1021/bi002449a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a New Buried Charge Drives a Large-Amplitude Protein Quake in Photoreceptor Activation

Abstract: Photoactive yellow protein (PYP) is a eubacterial photoreceptor and a structural prototype of the PAS domain superfamily of receptor and regulatory proteins. We investigate the activation mechanism of PYP using time-resolved Fourier transform infrared (FTIR) spectroscopy. Our data provide structural, kinetic, and energetic evidence that the putative signaling state of PYP is formed during a large-amplitude protein quake that is driven by the formation of a new buried charge, COO(-) of the conserved Glu46, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

47
466
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 229 publications
(514 citation statements)
references
References 31 publications
47
466
1
Order By: Relevance
“…The structure of PYP without the first 25 residues (termed ⌬25PYP) in the pB state has recently been investigated by NMR experiments (41) and parallel tempering molecular dynamics (MD) simulations (42). This structure is consistent with spectroscopic studies [FTIR (32), NMR (35,43,44), H/D exchange (37,45), fluorescence (46), and circular dichroism (40)] of the pB state in aqueous solution. That is, PYP partially unfolds its PAS domain during the photocycle, and this may be a key process in its signaling function (47).…”
Section: Background On the Photoactive Yellow Protein Systemmentioning
confidence: 63%
See 1 more Smart Citation
“…The structure of PYP without the first 25 residues (termed ⌬25PYP) in the pB state has recently been investigated by NMR experiments (41) and parallel tempering molecular dynamics (MD) simulations (42). This structure is consistent with spectroscopic studies [FTIR (32), NMR (35,43,44), H/D exchange (37,45), fluorescence (46), and circular dichroism (40)] of the pB state in aqueous solution. That is, PYP partially unfolds its PAS domain during the photocycle, and this may be a key process in its signaling function (47).…”
Section: Background On the Photoactive Yellow Protein Systemmentioning
confidence: 63%
“…The isolated protein displays photochemical activity based on the photoisomerization (32) of its p-coumaric acid (pCA) chromophore (33,34). Time-resolved visible (35,36) and FTIR (37) spectroscopic studies have revealed a series of intermediates in the PYP photocycle (38). The two states of PYP that are relevant to the work presented here are the initial dark state of PYP (pG) and the longest-lived intermediate (pB), which forms in 1 ms and thermally decays to the pG state on a second time scale.…”
Section: Background On the Photoactive Yellow Protein Systemmentioning
confidence: 99%
“…S1B and Table S5) only eight are located at the photoactive site of PYP (24). Of these residues, only Tyr42, Glu46, and Cys69 play a classical role as active site residues in that they serve as hydrogen bonding partners (20), proton donor (39), and cofactor attachment site (23). Fifteen highly conserved side chains are far removed from the active site.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging mechanism of receptor activation in PYP contains the following steps: (i) initial chromophore photoisomerization (32), which triggers (ii) active site proton transfer (33) that causes (iii) an electrostatically triggered protein quake (12), resulting in structural disruption of the PAS domain core, which is relayed (iv) to the N-terminal helices (13,14) by the side chain of Asn-43 (34). Future studies are needed to reveal how partial PAS domain unfolding contributes to signaling and whether this mechanism operates more widely in the PAS domain family.…”
Section: Discussionmentioning
confidence: 99%